How do you simplify #(-3x^2)(-4x^-2)#?

1 Answer
Mar 3, 2018

Answer:

See a solution process below:

Explanation:

First, rewrite the expression as:

#(-3 xx -4)(x^2 xx x^-2) =>#

#12(x^2 xx x^-2)#

Next, use this rule of exponents to combine the #x# terms:

#x^color(red)(a) xx x^color(blue)(b) = x^(color(red)(a) + color(blue)(b))#

#12(x^color(red)(2) xx x^color(blue)(-2)) =>#

#12x^(color(red)(2) + color(blue)(-2))#

#12x^(color(red)(2) - color(blue)(2))#

#12x^color(red)(0)#

Now, use this rule of exponents to complete the simplification:

#a^color(red)(0) = 1#

#12 xx 1 =>#

#12#